Propensity Score–Adjusted Comparison of Long-Term Outcomes Among Revascularization Strategies for Critical Limb Ischemia. (September 2019) - Mustapha, Jihad A.; Katzen, Barry T.; Neville, Richard F.; Lookstein, Robert A.; Zeller, Thomas; Miller, Larry E.; Nelson, Teresa R.; Jaff, Michael R.
Abstract : Background: Few studies have compared long-term outcomes among specific treatment modalities for critical limb ischemia. The aim of this study was to compare long-term outcomes with percutaneous transluminal angioplasty (PTA), stent placement, atherectomy, or surgical bypass in patients diagnosed with critical limb ischemia. Methods: In this observational study using Medicare claims data, we identified incident cases with a primary critical limb ischemia diagnosis who received PTA, stent placement, atherectomy, or surgical bypass. We used propensity score weighting to determine the association of treatment type with all-cause mortality and major (above ankle) amputation over 4 years follow-up. Results: Among 36 860 patients (10 904 PTA; 11 295 stent placement; 4422 atherectomy; 10 239 surgical bypass), all-cause mortality over 4 years was 49.3% with atherectomy, 51.4% with surgical bypass, 53.7% with stent placement, and 54.7% with PTA ( P <0.05 for all pairwise comparisons). Major amputation rates over 4 years were 6.8% with atherectomy, 7.8% with stent placement, 8.1% with PTA, and 10.8% with surgical bypass ( P <0.05 for all pairwise comparison except PTA versus stent). Conclusions: Among Medicare beneficiaries who received PTA, stent placement, atherectomy, or surgical bypass for critical limb ischemia, high mortality and major amputation rates were observed with minor differences among treatment groups. Statistically significant group differences of uncertain clinical importance were observed for several comparisons. Results from observational research may be susceptible to bias because of unmeasured confounders and, therefore, these comparative results should be interpreted with caution. Abstract : Supplemental Digital Content is available in the text.